1982
DOI: 10.1007/bf00007109
|View full text |Cite
|
Sign up to set email alerts
|

Overturn in a hypertrophic, warm, monomictic impoundment (Hartbeespoort Dam, South Africa)

Abstract: A major decrease in air temperature with an increase in wind stress created thermal instability resulting in overturn. Surface oxygen values decreased from 12.6 (170% saturation) prior to overturn to 0.4 mg . 1-l (5.7%) after overturn. Recovery of surface oxygen concentrations to supersaturation took approximately three months. Changes in the nitrogen balance after overturn indicated that extremely high rates of nitrification occurred. Little change in phosphorus concentration was observed. Surface chlorophyll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 26 publications
0
33
1
Order By: Relevance
“…Filtered (pre-rinsed Sartorius G/F filters) subsamples of the surface, middle and bottom samples were analyzed for ammonium-N, nitrite + nitrate-N, soluble reactive phosphorus (SRP) and silica (Si0 2) concentrations using auto-analyzers and the methods in Robarts et al (1982).…”
Section: Chemical Analysesmentioning
confidence: 99%
“…Filtered (pre-rinsed Sartorius G/F filters) subsamples of the surface, middle and bottom samples were analyzed for ammonium-N, nitrite + nitrate-N, soluble reactive phosphorus (SRP) and silica (Si0 2) concentrations using auto-analyzers and the methods in Robarts et al (1982).…”
Section: Chemical Analysesmentioning
confidence: 99%
“…This phosphorus can reach the epilimnion of the lake through diffusive processes such as have been described in Lake McIlwaine, Zimbabwe (Robarts & Ward, 1978). Robarts et al (1982) in examining the effect of overturn on the phosphorus status of Hartbeespoort Dam concluded that mixing processes affect the impoundment in direct proportion to the relative percentage of epilimnion and hypolimnion mixed. In recent years the shallow nature of the impoundment resulted in multiple mixing events (NIWR, 1985) which added phosphorus to the water column from the sediments; a low net sedimentation value was present during these periods which occurrred during early and late summer (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…By 1958, the lake was equated to an oxidation pond (Chomoky, 1958) whilst subsequent studies described the impoundment as eutrophic (Allanson & Gieskes, 1961;Toerien & Steyn, 1975;Scott etal., 1977) and hypertrophic (Scott et al, 1980;Ashton, 1985b;NIWR, 1985;Thornton et al, 1986). Massive hyperscums of Mcrocystis aeruginosa Kutz emend Elenkin occur regularly in sheltered embayments and inlets (Zohary, 1985) and virtually complete de-oxygenation of the water column following overturn is common (Allanson & Gieskes, 1961;Robarts et al, 1982;NIWR 1985). Robarts (1984) and Ashton (1985b) have described Hartbeespoort Dam as one of the most grossly impacted lakes yet studied.…”
Section: The Study Areamentioning
confidence: 99%
“…The high phosphorus flux in Hartbeespoort Dam would appear to be a function of the extremely enriched (Robarts et al, 1982) and highly productive nature of the impoundment (Robarts, 1984) .…”
Section: Discussionmentioning
confidence: 99%